La production de logements en Belgique et à Bruxelles – Acteurs, dynamiques, géographie - Christian Dessouroux; Alice Romainville (EchoGéo)
The Belgian residential landscape has considerably changed since the 1950s. If economic activity and collective housing continue to be concentrated in urban areas, the proliferation of single-family dwellings in suburban areas - dating back to the 19th century - continues unabated. Other developments are more recent, such as an increase in refurbishments and conversions of existing buildings, fuelled by among other things the insufficient production of new housing and a revaluation of older housing.This article provides an overview of residential construction in Belgium since the 1950s, focusing particularly on more recent changes using statistical resources that have yet to be fully explored. Through an analysis of building permits issued since 1996, we will try to highlight the particularities of the Belgian context and to reveal the most significant changes in terms of housing production, both quantitatively and geographically. The relative importance of public and private agents on the housing market will be studied using the example of the Brussels Region, for which very accurate data has been used.